Ethics of the Use of Artificial Intelligence (AI) in the Paradigm of Islamic Law - Mulki Firdaus Alamsyah; Yayuli; Ahmad Remanda (Walidem Institute and Publishing, 2026)
Objective: The principal objective of this scholarly inquiry is to meticulously examine the ethical implications of artificial intelligence (AI) within the context of Islamic jurisprudence, with a distinct focus on the principles of maqosid al-shari‘ah (the paramount objectives of Islamic law) serving as a moral and legal foundation for the evaluation of AI applications. Theoretical framework: The theoretical foundations of this investigation are derived from Islamic legal and ethical philosophy, specifically the five fundamental values of maqosid al-shari‘ah, safeguarding of faith, life, intellect, lineage, and property employed as evaluative criteria to assess the integration of technology within Muslim societies. Literature review: A diverse array of primary sources, including the Qur’an and Hadith, is meticulously scrutinized alongside contemporary Islamic scholarship that addresses the intersection of ethics and technology. Previous research on Islamic ethics in the digital and biomedical spheres is referenced, elaborated upon, and critically appraised to ensure a contemporary and contextually relevant analysis. Methods: This investigation adopts a qualitative methodology based on an exhaustive literature review. Primary religious texts and secondary academic discourses concerning AI ethics and Islamic law are analyzed through thematic content analysis to develop a normative framework that harmonizes Shariah principles with emerging AI technologies. Results: The findings of this research indicate that while AI offers substantial benefits in areas such as healthcare, education, and governance, it simultaneously presents ethical challenges, including issues related to surveillance, algorithmic bias, and a reduction in human accountability. From an Islamic standpoint, AI should not replace human moral agency but rather enhance it. Justice, accountability, and the welfare of the community must remain of utmost importance in its application. Implications: This study highlights the urgent need for interdisciplinary dialogue between Islamic scholars and technology developers, the promotion of Islamic ethical awareness among Muslim AI practitioners, and the establishment of fatwas and Shariah-compliant regulatory frameworks to ensure the ethical incorporation of AI into Muslim societies. Novelty: This research offers a noteworthy contribution to the burgeoning field of Islamic AI ethics by providing a structured, Shariah-aligned ethical framework for the assessment and guidance of AI technologies. It underscores the adaptability of Islamic jurisprudence in addressing contemporary innovations while remaining steadfastly anchored in enduring ethical principles.